An iterative approach for curvature ductility of RC beams at high strain rates - Pandey, Akhilesh K. (Journal of Structural Engineering, 2024)
An iterative approach for computation of curvature ductility factor for doubly reinforced concrete sections has been proposed by taking into account strain rate sensitive properties of concrete and steel, confi nement of core concrete and degradation of cover concrete during load reversal under earthquake loading. With the ongoing research activity for the evolution of performance based seismic design proper quantification of ductility with a simplified approach may be required in day today seismic design. The available curvature ductility of reinforced concrete rectangular sections with a range of tension and compression steel ratios for confi ned and unconfi ned concrete has been computed using the proposed approach at a strain rate varying from 3.3 × 10⁻⁵ to 1.0/sec encountered during static and earthquake loading. The parametric studies have indicated that curvature ductility factor decreases at higher strain rates. Percentage decrease is more for a richer mix concrete with the similar reinforcement. The confinement effect has marked influence and increase in ductility is more than twice for confined concrete (0.6 percent volumetric ratio of transverse steel) compared to unconfined concrete. The various codal provisions for providing required ductility in moment resisting frames has been discussed.